Parmenidas ir M. Karagatsis (mito atspindys literatūroje) - Goncharko, Oksana; Eloeva, Fatima; Romanenko, Yury (Literatūra, 2020)
The paper aims to show some structural parallels between the concept of motion as developed by Parmenides (5th c. BC) and the expression of the phenomena of motion in the story A Solitary Voyage to the Island Cythera by the Greek writer M. Karagatsis (1908–1960). The novelette of M. Karagatsis is interpreted as a parmenidean “motionless motion” reflexion. It is argued that M. Karagatsis’s story is structurally and essentially related to the Parmenidean poem On Nature, treating the consideration of motion as one of the impossible properties of being; and more obviously refers to certain poems by Constantine Cavafy (1863–1993), which also contain the idea of the meaninglessness of the difference between κίνησις and ἀκινησία. Thus, the concepts of κίνησις and ἀκινησία in the story by M. Karagatsis echo both the Parmenidean ideas and the Cavafy’s images of movement.
Keywords: Parmenidas; M. Karagatsis; recepcija; judesio samprata; metafora; ontologija